La administración financiera comercial y la gestión del riesgo crediticio: Análisis desde la óptica del Sistema de Administración de Riesgo Crediticio (SARC) aplicado por las entidades financieras, y los modelos de análisis de riesgo. Caso Colombia. (2025)
The integration of financial systems in recent times has made clear the need to establish regulatory frameworks that protect investors. Precisely within the economic market, financial institutions carry out credit operations, and these transactions must be sufficiently secure to avoid compromising the corporate portfolios of these organizations that channel resources towards deficit agents; With a view to this objective, it has become imperative to structure a centralized information model that allows defining the criteria related to the determination of guarantees, real payment capacities, credit history and the economic allocation of the resources granted to potential applicants, thereby avoiding generating an asymmetry in the data networks available to make balance transfer decisions.